THE RELATIONSHIP BETWEEN ANTHROPOMETRIC PARAMETERS AND BODY MASS INDEX WITH BLOOD GLUCOSE LEVEL: AN ANALYTICAL STUDY - Pauzi, Rizqi Yanuar; Wahyudin, Wahyudin; Nur'aini, Indah (Medical and Health Journal, 2025)
This study aims to analyze the relationship between body weight, height, body mass index (BMI), and blood glucose levels among 105 study subjects . Descriptive analysis results show that the average body weight of subjects is 64.81 kg, height is 1.62 m, and blood glucose level is 107.05 mg/dl, with significant variation in glucose levels. Scatter plots indicate that blood glucose does not have a significant relationship with body weight and height, while there is a tendency for increased blood glucose levels with increasing BMI. Correlation analysis reveals a strong positive relationship between body weight and BMI, but blood glucose does not show significant relationships with other variables. Using quantile regression, the analysis shows no significant relationship between independent variables and blood glucose at the median quantile. These findings highlight the need for further research to understand the factors influencing blood glucose levels and the importance of comprehensive assessment of anthropometric parameters.